Ameliorative effect of black grape juice on systemic alterations and mandibular osteoradionecrosis induced by whole brain irradiation in rats. (1st February 2017) - Freitas, Robson B.; González, Paquita; Martins, Nara Maria B.; Andrade, Edson R.; Cesteros Morante, María Jesús; Conles Picos, Iban; Costilla García, Serafín; Bauermann, Liliane F.; Barrio, Juan Pablo
Abstract: Purpose: Whole brain irradiation (WBI) causes a variety of secondary side-effects including anorexia and bone necrosis. We evaluated the radiomodifying effect of black grape juice (BGJ) on WBI alterations in rats measuring food and water intake, body weight, hemogram, and morphological and histological mandibular parameters. Materials and methods: Forty male rats (200–250 g) were exposed to eight sessions of cranial X-ray irradiation. The total dose absorbed was 32 Gy delivered over 2 weeks. Four groups were defined: (i) NG: non-irradiated, glucose and fructose solution-supplemented (GFS); (ii) NJ: non-irradiated, BGJ-supplemented; (iii) RG: irradiated, GFS-supplemented; and (iv) RJ: irradiated, BGJ-supplemented. Rats received daily BGJ or GFS dosing by gavage starting 4 days before, continuing during, and ending 4 days after WBI. Results: RJ rats ingested more food and water and showed less body weight loss than RG rats during the irradiation period. Forty days after WBI, irradiated animals started losing weight again compared with controls as a consequence of masticatory hypofunction by mandibular osteoradionecrosis (ORN). Osteoclastic activity and inflammation were apparent in RG rat mandibles. BGJ was able to attenuate the severity of ORN as well as to improve white and red blood cell counts. Conclusions: Fractionated whole brain irradiation induces mandibular changes that interfere with normal feeding. BGJ can be used to mitigate systemic side-effects of brain irradiation and ORN.